Associations between lifestyle factors and body mass index in African-American community college students. Issue 7 (26th October 2021) - Stephens, Janna; Tan, Alai; Miller, Hailey; Perkins, Antoinette
Abstract: Objective: The goal was to examine associations between body mass index (BMI) and lifestyle factors in African American community college students. Methods: Young adults, 18–25, who identified as African American were eligible to participate from 3/17 to 11/17. BMI, body image, discrimination, social roles, emotional and informational support, nutrition knowledge, and physical activity were assessed. Results: Data from 323 students were analyzed. The mean age was 20.1 ± 2.0 years. There were no significant differences between individuals with BMI ≥ 25 and BMI < 25 on social role satisfaction, discrimination, and emotional or informational support. Overweight/obese individuals rated themselves higher on body image than normal weight individuals. The association between ideal body image and BMI sustained after adjusting for various factors. Conclusions: This is a unique population and they have unique needs in weight loss interventions. The strong relationship between body image and BMI suggests that incorporating body image into intervention design may assist in weight loss.